Quality of Working Life (A Study of Government Schools of District Amritsar) - Kaur, Kawaljit; Chaudhary, Sonika (Journal of Commerce and Trade, 2009)
The concept of the ‘Quality of Working life’ is imprecise and thus problematic to operationalise. As per the present scenario whether is banking sector , pharmaceutical or Fast Moving Consumer Goods (FMCG) everything has been made target oriented. Under such system of working, the employees have to pay in terms of increasing work pressure, ascending stress and stress related problems are alarming proportions. Hence, the purpose of my study i.e. quality of working life (in particular among teachers). Here “Quality of working life” is abbreviated as QWL. In short the above analysis showed that QWL in govt. schools is good but still there are many schools available in rural areas where facilities are provided but there is lack of many facilities. So, to improve the overall QWL in govt. schools rural areas schools should be given more attention.